DILÂLAH MAKNA RÛH DALAM PENAFSIRAN IBNU KATSÎR - Pane, Ismail (Yayasan Baitul Hikmah al-Zain, 2024)
This paper aims to elaborate the meaning of the word Ruh. Although Allah has sent down the Qur'an in clear Arabic, not all Muslims understand and understand the meaning of the words contained in the Qur'an. Especially regarding the meaning and interpretation of the word Ruh. Ibn Katsr in interpreting Dilâlah the meaning of Ruh in the Qur'an, where in general the meaning of the word Ruh contains the meaning of something that makes living beings (souls), and also means the angel Gabriel or the Qur'an, even help from Allah. However, in interpreting the meaning of Ruh in the Qur'an, he does not give an opinion or thought explicitly about the meaning of Ruh, only provides an explanation of the opinions of other scholars. Furthermore, Ibn Katsr in interpreting the meaning of the verse regarding the word Ruh uses the hadith of the Prophet Muhammad. and the words of friends, and rarely use or quote the words of other scholars of interpretation.